2013
DOI: 10.1186/1756-0500-6-159
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from a community based intervention to improve injection safety in Pakistan

Abstract: BackgroundA national study in 2007 revealed that in Pakistan the prevalence of hepatitis B is 2.5% and for hepatitis C it is 5%. Unsafe injections have been identified as one of the reasons for the spread of these infections. Trained and untrained providers routinely perform unsafe practices primarily for economic reasons i.e. they reuse injection equipment on several patients. The patients, do not question the provider about the need for an injection because of social barriers or whether the syringe is coming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
2
10
0
1
Order By: Relevance
“…In 2015, WHO launched new injection safety guidelines 184 , which included a recommendation that by 2020 all Member States should switch to exclusive use of safety engineered injection devices. Motivated by this recommendation, a study based in a large district in rural Pakistan showed that a communitybased intervention designed to improve knowledge and practice of safe medical injections could substantially improve both awareness of the association between unsafe injections and viral hepatitis and clinical practice (eg, an increase in reported use of new needles from 15% to 29between 2011 and 2012) 185 . In India, high-level political engagement has led to initiatives within the State of Punjab, including establishment of 40 model injection safety centres at district-level health facilities and medical and nursing institutes throughout the State, which also serve as a training resource for health workers on injection safety and reuse-prevention measures.…”
Section: Success Stories and Ongoing Challenges [H3]mentioning
confidence: 99%
“…In 2015, WHO launched new injection safety guidelines 184 , which included a recommendation that by 2020 all Member States should switch to exclusive use of safety engineered injection devices. Motivated by this recommendation, a study based in a large district in rural Pakistan showed that a communitybased intervention designed to improve knowledge and practice of safe medical injections could substantially improve both awareness of the association between unsafe injections and viral hepatitis and clinical practice (eg, an increase in reported use of new needles from 15% to 29between 2011 and 2012) 185 . In India, high-level political engagement has led to initiatives within the State of Punjab, including establishment of 40 model injection safety centres at district-level health facilities and medical and nursing institutes throughout the State, which also serve as a training resource for health workers on injection safety and reuse-prevention measures.…”
Section: Success Stories and Ongoing Challenges [H3]mentioning
confidence: 99%
“…Community approaches that reduce information asymmetry between providers and patients have been promising (28). One intervention in Tando Allah Yar improved patient awareness from 15% to 29% within 6 months (29). Other complementary approaches may be to brand as safe providers those that visibly do not reuse syringes.…”
Section: Research Articlementioning
confidence: 99%
“…10,11 However, it also pointed to the absence of improvement in reducing the frequency of analgesics, vitamins or anti-histamines in the desire to meet user demand. 15,16 Reducing injection overuse would only be a matter of promoting rational use of medicines if injections were administered safely. 17 However, reuse of syringes frequently leads to transmission of bloodborne pathogens.…”
Section: Regional Variationsmentioning
confidence: 99%